Admissions for isolated nonoperative mild head injuries: Sharing the burden among trauma surgery, neurosurgery, and neurology. Issue 4 (October 2016) - Zhao, Ting; Mejaddam, Ali Y.; Chang, Yuchiao; DeMoya, Marc A.; King, David R.; Yeh, Daniel D.; Kaafarani, Haytham M.A.; Alam, Hasan B.; Velmahos, George C.
Abstract : BACKGROUND: Isolated nonoperative mild head injuries (INOMHI) occur with increasing frequency in an aging population. These patients often have multiple social, discharge, and rehabilitation issues, which far exceed the acute component of their care. This study was aimed to compare the outcomes of patients with INOMHI admitted to three services: trauma surgery, neurosurgery, and neurology. METHODS: Retrospective case series (January 1, 2009 to August 31, 2013) at an academic Level I trauma center. According to an institutional protocol, INOMHI patients with Glasgow Coma Scale (GCS) of 13 to 15 were admitted on a weekly rotational basis to trauma surgery, neurosurgery, and neurology. The three populations were compared, and the primary outcomes were survival rate to discharge, neurological status at hospital discharge as measured by the Glasgow Outcome Score (GOS), and discharge disposition. RESULTS: Four hundred eighty-eight INOMHI patients were admitted (trauma surgery, 172; neurosurgery, 131; neurology, 185). The mean age of the study population was 65.3 years, and 58.8% of patients were male. Seventy-seven percent of patients has a GCS score of 15. Age, sex, mechanism of injury, Charlson Comorbidity Index, Injury Severity Score, Abbreviated Injury Scale in head and neck, and GCS were similar among the three groups. Patients who were admitted to trauma surgery, neurosurgery and neurology services had similar proportions of survivors (98.8% vs 95.7% vs 94.7%), and discharge disposition (home, 57.0% vs 61.6% vs 55.7%). The proportion of patients with GOS of 4 or 5 on discharge was slightly higher among patients admitted to trauma (97.7% vs 93.0% vs 92.4%). In a logistic regression model adjusting for Charlson Comorbidity Index CCI and Abbreviated Injury Scale head and neck scores, patients who were admitted to neurology or neurosurgery had significantly lower odds being discharged with GOS 4 or 5. While the trauma group had the lowest proportion of repeats of brain computed tomography (61.6%), the neurosurgery group had the highest proportion of intensive care unit admission (29.8%), and the neurology group had the longest emergency department stay (7.5 hours), there were no significant differences in duration of hospital stay, in-hospital complications, and readmission within 30 days. CONCLUSIONS: Although there were differences in use of health care resources, and the proportion of patients with GOS of 4 or 5 on discharge was slightly higher among patients admitted to trauma, most clinical outcomes were similar in INOMHI patients admitted to trauma surgery, neurosurgery, or neurology in our institution. A rotational policy of admitting INOMHI patients is feasible among services with expertise in and commitment to the care of these patients. LEVEL OF EVIDENCE: Therapeutic/care management study, level IV.